KUALITAS LINGKUNGAN PERMUKIMAN DI DATARAN DAN PERBUKITAN - Inayah Hidayati (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
The research took three villages in Kulon Progo Regency which have different physiography, Kalirejo Village as hilly areas, Tayuban and Pleret Village as plains. The research employs survey methods, which take samples from a population and apply questionnaires as a primary mean of collecting the data. The research showed (1) there is significant difference of settlement environment quality between plain and hills territory. The plain territories have a better quality than hills territories in settlement environment quality. (2) The dominant factor corresponding to settlement environment quality is slope factor. The meaning of this, a settlement environment with plain slope (plain territory) has a better settlement environment quality than settlement environment with steep slope (hills territory). (3) Slope, groundwater level, and the level of family income have a significant correlation with the settlement environment quality.